Assessment of Myocardial Dysfunction by Three-Dimensional Echocardiography Combined With Myocardial Contrast Echocardiography in Type 2 Diabetes Mellitus - Li, Wei; Lv, Xiao-zhou; Liu, Jia; Zeng, Jia-hui; Ye, Min; Li, Cui-ling; Fan, Rui; Lin, Hong; Huang, Hui-ling; Yao, Feng-juan (Frontiers in Cardiovascular Medicine, 2021)
Background We aimed to explore the value of combining real-time three-dimensional echocardiography (RT-3DE) and myocardial contrast echocardiography (MCE) in left ventricular (LV) evaluating myocardial dysfunction in type 2 diabetes mellitus (T2DM) patients. Patients and Methods A total of 58 T2DM patients and 32 healthy individuals were selected for this study. T2DM patients were further divided into T2DM without microvascular complications (n=29) and T2DM with microvascular complications (n=29) subgroups. All participants underwent RT-3DE and MCE. The standard deviation (SD) and the maximum time difference (Dif) of the time to the minimum systolic volume (Tmsv) of the left ventricle were measured by RT-3DE. MCE was performed to obtain the perfusion measurement of each segment of the ventricular wall, including acoustic intensity (A), flow velocity (β), and A·β. Results There were significant differences in all Tmsv indices except for Tmsv6-Dif among the three groups (all P < 0.05). After heart rate correction, all Tmsv indices of the T2DM with microvascular complications group were prolonged compared with the control group (all P < 0.05). The parameters of A, β, and A·β for overall segments showed a gradually decreasing trend in three groups, while the differences between the three groups were statistically significant (all P < 0.01). For segmental evaluation of MCE, the value of A, β, and A·β in all segments showed a decreasing trend and significantly differed among the three groups (all P < 0.05). Conclusions The RT-3DE and MCE can detect subclinical myocardial dysfunction and impaired myocardial microvascular perfusion. Left ventricular dyssynchrony occurred in T2DM patients with or without microvascular complications and was related to left ventricular dysfunction. Myocardial perfusion was reduced in T2DM patients, presenting as diffuse damage, which was aggravated by microvascular complications in other organs. Keywords: Diabetes mellitus; Myocardial dysfunction; Three-dimensional echocardiography; Myocardial contrast echocardiography